Frequency and Clinical Risk Factors of Pneumonia among Children with Cerebral Palsy: Pneumonia among Children with Cerebral Palsy - Hajira, Bibi; Pervez, Sana; Ashraf, Seema; Farid, Alvina; Khan, Arif Mehmood; Qadeer, Asma Abdul (Pakistan Journal of Health Sciences, 2025)
Children with cerebral palsy (CP) are prone to various comorbidities, among which pneumonia is a leading cause of morbidity and hospitalization. Early identification of contributing factors is crucial to minimize respiratory complications. Objectives: To determine the frequency of pneumonia and identify associated clinical risk factors among children diagnosed with cerebral palsy. Methods: This cross-sectional study was conducted at the Pediatrics Unit, Khyber Teaching Hospital, Peshawar, for six months. Ninety-three children with confirmed CP were enrolled through consecutive sampling. Data on demographics, feeding methods, CP severity, nutritional status, immunization, and aspiration history were collected. Pneumonia was diagnosed clinically and radiologically. Statistical analysis was performed using SPSS version 26.0, and associations were tested using the Chi-square. Results: Among 93 children, 38 (40.9%) had pneumonia. Strong associations were observed with aspiration history (χ² = 85.14, p<0.001, Cramer’s V = 0.957), feeding method (χ² = 32.13, p<0.001, Cramer’s V = 0.588), immunization status (χ² = 74.72, p<0.001, Cramer’s V = 0.896), and nutritional status (χ² = 52.32, p<0.001, Cramer’s V = 0.750). Interestingly, no pneumonia cases occurred in children with severe CP or those who were severely malnourished. Conclusions: Pneumonia is highly prevalent in children with CP and is strongly linked to aspiration and oral feeding. Unexpected findings, such as the absence of pneumonia in severe CP and malnourished children, highlight the need to consider contextual exposure and monitoring factors. Targeted prevention strategies, including caregiver education, aspiration management, and individualized nutritional support, are essential to reduce respiratory complications in this vulnerable population.